A comprehensive analysis of silicon photonic switching chips - Ahmad, Hasnain; Gulzar, Muhammad Majid; Habib, Salman; Ahmed, Ijaz; Malik, Saddam Hussain; Bhatti, Muhammad Kamran (Optical and quantum electronics, 2025)
Recently, interest has increased in the flexibility of silicon-integrated photonic system design with the complementary metal-oxide semiconductor (CMOS) advancements, which enables low-cost and large-scale production. The photonic switch is an essential component of optoelectronic microchips, with widespread applications in fibre optic telecommunications and communication systems, optical data storage, and monitoring devices like LiDAR. Most silicon-integrated photonic switches use either the thermo-optical or scattering effect in transmission to send signals in different ways. However, the transmission scattering phenomenon is limited by a negligible change in refractive index, while the thermo-optical action results in significant energy consumption. These effects are inefficient as they require continuous power consumption, even when toggling is unnecessary. Phase-change metals (PCMs) were implemented into silicon-integrated optic switching as a means of addressing such limitations. In this study, we categorised silicon-integrated optical switches by their internal mechanisms and discussed the most advanced literature on the subject. We additionally take a look at the latest research on PCM-integrated optical switches built on silicon. There is also a comparison and discussion of the benefits and drawbacks of embedded optical switches that either utilize or do not use PCMs.